Top 10 Tech Cars It's The Environment, Stupid. - Voelcker, J.
This paper has described the carbon emission from vehicles and its impact on environmental factors in Europe. The author has considered that Europe is debating not whether to cut carbon emissions from vehicles but simply when to do it and by how much. The average new car on Europe's roads now emits roughly 160 grams of carbon dioxide per kilometer; the European Commission proposed last year to lower that to 130 g/km by 2012. But Europe's carmakers seem likely to have missed a voluntary 2008 target of 140 g/km. Biofuel is one of the reason making the environment black, according to one of the car maker. This paper has also explained the hurdles due to CO2 emission in hybrid electric vehicles in some parts of the Asia.
Keywords: European Commission; European carmakers; Biofuel; Car; Carbon emission; Hybrid electric vehicles